Seven reasons why binary diagnostic categories should be replaced with empirically sounder and less stigmatizing dimensions - Lahey, Benjamin B.; Tiemeier, Henning; Krueger, Robert F. (JCPP advances, 2022)
Background An ongoing positive revolution advocates a new approach to the individual differences in human emotions, cognitions, and behavior that cause distress and impair functioning. This revolution endorses the long‐proposed, but still unrealized rejection of the medical model, which attributes psychological problems to a sick brain or mind. In addition, it advocates replacing the binary diagnoses used in ICD and DSM, which assume a clear discontinuity between “normal” and “abnormal” functioning, with continuous dimensions of psychological problems. Method Selective literature review. Results and Discussion Seven strong reasons are provided for adopting a dimensional approach. Seven logical and empirical reasons are provided for replacing binary diagnostic categories with more valid and less stigmatizing dimensions of psychological problems.